Metaverse in Tourism and Hospitality: Empirical Evidence on Generation Z from Italy - Rancati, Elisa; d’Agata, Alessandro (European Scientific Journal, ESJ, 2022)
The paper has been conducted to analyze the change taking place in tourism marketing due to the metaverse innovation through tastes and needs of today’s new generations of tourists, especially generation Z, that will be the future customers of the next decades. The goal of this study has been to analyze the opportunities concerning the metaverse and its immersive technology, through a survey conducted on a sample of generation Z people and understand which are the practical implications that can guide tourism companies and territorial governments’ decisions during the nearest future, to satisfy new market demand and optimize their communication in the metaverse.